BEHAVIORAL AND VOCAL CHARACTERISTICS OF LAYING HENS^UNDER DIFFERENT HOUSING AND FEEDING CONDITIONS - N. Y. Kim; S. Y. Jang; S. J. Kim; B. T. Jeon; M. R. Oh; E. K. Kim; H. J. Seong; Y. J. Tang; Y. S; Yun 1^and S. H. Moon1 (Journal of Animal and Plant Sciences, 2017)
We analyzed the behavioral and vocal characteristics of laying hens in this study, with the aim of assessing the level of animal welfare in laying hen flocks in South Korea. Sixty- four hens (farm A:n=18, farm B:n=18, farm C:n=28) at three farms under different housing and feeding conditions were observed. We analyzed their eating, exploring, resting, preening, ^and aggressive feather pecking, as well as special vocalizations with three replications. Time spent on eating for farm C was higher than for farm A (P<0.05). Time spent resting was higher in birds at farm B than those at farm C (P<0.05). Time spent eating increased as the group size increased and width of the cage declined, whereas resting and preening tended to increase as the group size and eating time decreased. Two special vocalizations squawk and alarm calls were more frequently recorded at high stocking density. Recording vocalizations could be a useful method to support the analysis of behavior in laying hens. The group size, width of the cage, stocking density, feeding frequency and feeding time were major factors affecting the behavior and vocalization patterns in laying hens. Analysis of these key factors may be utilized as a useful method to measure the level of animal welfare in actual hen farms where various environmental factors worked compositely.
Keywords: Animal welfare; Behavior; Group size; Hy-line Brown; Laying hens; Vocalization